Common Research Study Designs Used in Homoeopathy (Advancements in Homeopathic Research, 2022)
Research in Homoeopathy helps in generating, validating and consolidating scientific evidences of medications and treatment regimes. These researches are useful in prevention and treatment of various diseases. The World Health Organisation (WHO) has, from time to time, affirmed that all national and international health policies should be laid on the foundation of good researches. A good research is most importantly based upon the selection of aappropriate study design. A design should be used which gives most definitive answers to the research question with available sources and material. All types of research designs have their own pros and cons. It depends on the researcher which design to choose and which not to. This article deals with various types of research study designs adopted for research in Homoeopathy with their advantages, disadvantages and examples of published research studies with such study designs.
Keywords: Research studies; Homoeopathy; Study designs